Hubungan Ketahanan Pangan dengan Status Gizi Ibu Balita di Kecamatan Selo Boyolali - Makhabatien Salmania; Luluk Ria Rakhma; Siti Nurokhmah (Yayasan Literasi Sains Indonesia, 2026)
Fulfillment of family nutritional needs is associated with household food security conditions. This study aimed to analyze the relationship between household food security and the nutritional status of mothers with toddlers in Selo District, Boyolali Regency, including Jrakah, Klakah, and Tlogolele Villages. This study used an analytical observational design with a cross-sectional approach involving 108 mothers of toddlers selected through simple random sampling. Household food security was assessed using the Household Food Insecurity Access Scale (HFIAS), while nutritional status was determined based on Body Mass Index (BMI). The relationship between variables was analyzed using the Chi-Square test with a significance level of p<0.05. The results showed that 51.9% of households experienced food insecurity and 8.3% of mothers with toddlers had undernutrition. There was a significant relationship between household food security and the nutritional status of mothers with toddlers (p=0.033). Mothers from food-insecure households had an 8.5 times higher likelihood of experiencing undernutrition compared to those from food-secure households (OR=8.50; 95% CI: 1.024–70.524). Maternal nutritional status is influenced by various factors, including socioeconomic conditions, dietary patterns, energy intake, physical activity, and biological factors.